2020
DOI: 10.13106/jafeb.2020.vol7.no6.209
|View full text |Cite
|
Sign up to set email alerts
|

How Destination Image Factors Affect Domestic Tourists Revisit Intention to Ba Ria-Vung Tau Province, Vietnam

Abstract: This research examines the affect of destination image factors on revisit intention of domestic tourists at Ba Ria Vung-Tau (BRVT), by questioning directly 510 domestic tourists. The convenient sampling method is used in dividing the crowds into four groups; the four main surveyed areas in BRVT are: Vung Tau, Long Hai-Phuoc Hai, Xuyen Moc and Con Dao. A combination of qualitative and quantitative methodologies were utilized. A focus group of 10 domestic tourists was set up to review and explore the various fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…The results showed that accessibility significantly and positively affects tourists' return intentions (Ngoc, Trinh, 2015). Another study by Giao et al (2020) investigated the factors that affect domestic tourists' revisit intentions using a sample of 550 domestic tourists who had visited Vietnam in the last quarter of 2019. The findings showed that accessibility is positively associated with revisit intentions.…”
Section: Accessibilitymentioning
confidence: 99%
“…The results showed that accessibility significantly and positively affects tourists' return intentions (Ngoc, Trinh, 2015). Another study by Giao et al (2020) investigated the factors that affect domestic tourists' revisit intentions using a sample of 550 domestic tourists who had visited Vietnam in the last quarter of 2019. The findings showed that accessibility is positively associated with revisit intentions.…”
Section: Accessibilitymentioning
confidence: 99%
“…This is similar with Marasigan and Borbon, (2021) stating that these infrastructure facilities are given so much attention by the resort management, but customers, since they have expectation on this, give focus of their observation on how the entire resort looks like, thus, the customers look at the place as a whole. Tourism infrastructure that fulfills the demands of tourists and provides simple access to places can help to improve the destination's image and increase visitors' desire to return (Giao et al, 2020). Fast internet connection is one of the things that guests who enjoy uploading their holiday activities and conducting live streaming consider while picking their chosen place.…”
Section: International Journal Of Research Studies In Management 109mentioning
confidence: 99%
“…The destination image, which is produced by a mix of destination qualities, is an essential component in enticing people to come and motivating them to return. (e.g., beautiful landscape, shopping opportunities, cultural exchange, infrastructure, safety, and activities) (Giao et al, 2020). However, tourism activities also have negative influences on the environment, in which solid waste is one of the most significant impacts.…”
Section: International Journal Of Research Studies In Management 111mentioning
confidence: 99%
“…On the other hand, in the heart of researches, the psychological factors (Chen et al, 2020), destination image (Elahi et al, 2020), a desire for variety, the environment, infrastructure, recreation and entertainment, local food, mobility, and price value, and atmosphere (Giao et al, 2020), destination attributes including cognitive and affective evaluation (Jumanazarov et al, 2020), destination brand engagement factors (Kumar & Kaushik, 2020), sustainability and environmental awareness (Kusumawati et al, 2020), quality of service, corporate image, and customer satisfaction (Khoo, 2022), etc. have explored to create the revisit intention in the different destinations rather than Bangladesh.…”
Section: Introductionmentioning
confidence: 99%